2021
DOI: 10.2495/eq-v6-n4-371-381
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency in industry 4.0: assessing the potential of industry 4.0 to achieve 2030 decarbonisation targets

Abstract: The energy transition for the industrial sector is not limited to a reduction in energy consumption: the real issue is to combine sustainability with growth, by mixing the two ingredients (the rational energy use and the industrial growth) which are not always compatible. The National Energy and Climate Plan (NECP) and the New Green Deal policies in Italy have the goal to promote an economic development as well as the environment sustainability and social inclusion. RSE 1 has investigated the role of the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Unlike Doroshuk (2021), Maggiore et al (2021), Parmar et al ( 2022), Qi et al (2022), it has been proven that in the era of artificial intelligence there are no obstacles to decarbonization, but on the contrary, new opportunities have been created for this. Using only disruptive innovations of industry 4.0 (for example, only robots) can hinder the reduction or even increase the number of carbon emissions, as well as slow down the transition to "clean" energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Doroshuk (2021), Maggiore et al (2021), Parmar et al ( 2022), Qi et al (2022), it has been proven that in the era of artificial intelligence there are no obstacles to decarbonization, but on the contrary, new opportunities have been created for this. Using only disruptive innovations of industry 4.0 (for example, only robots) can hinder the reduction or even increase the number of carbon emissions, as well as slow down the transition to "clean" energy.…”
Section: Discussionmentioning
confidence: 99%
“…And "clean" energy today is not able to cover the growing demands of the economy in energy, which does not allow reduction and may even lead to a forced growth in carbon emissions. In this regard, in the works of Doroshuk (2021), Maggiore et al (2021), Parmar et al (2022, Qi et al (2022), the AI era is considered an unfavourable time and an unfriendly technological landscape for decarbonization.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Maggiore et al (2021), Morelli et al (2022), Wachnik et al (2022), andZaidan et al (2022), it was justified that, in order to take advantage of the use of advanced technologies of Industry 4.0 in the energy economy, it is advisable to actively use them only in entrepreneurship, while their use in society and the state does not provide advantages with the current approach to the development of the energy economy based on Industry 4.0 technologies. The reasoning of this conclusion is based on the revealed absence of a positive contribution of the government AI Readiness Index to the sustainability of energy.…”
Section: Discussionmentioning
confidence: 99%
“…In the works of Amir et al (2022), Chen et al (2022), Favi et al (2022), and Vlasov et al (2019, the use of advanced Industry 4.0 technologies in the energy economy provides advantages in both production and distribution processes. Maggiore et al (2021), Morelli et al (2022), Wachnik et al (2022), andZaidan et al (2022) indicated that, in order to fully take benefit of the advanced technologies of Industry 4.0 in the energy economy, it is advisable to actively use them by representatives of all interested parties: energy companies, state regulators of the energy economy, and energy consumers. Baxter (2012), Inshakov et al (2019), Kabeyi and Olanrewaju (2022), Kapitonov et al (2019), Kluczek et al (2021), andRatner et al (2022) stated that the digitalization of the energy economy based on advanced technologies of Industry 4.0 is universal-it is suitable for all countries, regardless of their energy efficiency, role, and position in global energy markets.…”
Section: Digital Energetics Based On the Technologies Of Industry 40:...mentioning
confidence: 99%
See 1 more Smart Citation